RETRACTED: Influence of environmental factors on physiological state of domestic yak (Bos mutus) (on the example of the Steppe Research Station “Orenburg Tarpania”) - Platonov Stanislav; Grudinin Dmitrij (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001